20 years of research in microfinance: An information management approach. (August 2019) - Gutiérrez-Nieto, Begoña; Serrano-Cinca, Carlos
Highlights: The paper reviews 1874 microfinance papers published from 1997 to 2017. It performs an information management analysis of the microfinance field. The review is based on bibliometric data. Keyword co-occurrence networks and citation networks were exploited for knowledge mapping. Abstract: In the last 20 years, microfinance has moved from a promise to reality, although with ups and downs. This paper reviews 1874 papers published from 1997 to 2017 to perform a scientometric analysis of the microfinance field. The literature review is based on bibliometric data: keyword co-occurrence networks and citation networks were exploited for knowledge mapping. Data analysis shows the two research traditions: papers focusing on clients (welfarists) and papers focusing on microfinance entities themselves (institutionalists). Institutionalism, which had little presence in the early research in microfinance, now exhibits great strength. A chronological analysis reveals the evolution of the topics most interesting to researchers: the first stage described the innovations of the microcredit practices and their impact; the second and very expansive stage in which microfinance institutions' peculiarities were analyzed; and nowadays the sector is mature but with negative aspects arising, such as mission drift. The keywords analysis discovers emerging research topics, shows the use of sophisticated techniques, and recognizes an emerging trend of the sector: achieving financial inclusion.